PEMANTAU KESTABILAN TEGANGAN PADA JARINGAN LISTRIK 3-FASE BERBASIS PC DATALOGGER - Hani, Slamet (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
This research, is studied about a system of PC Datalogger capable to measure, record, present the graph of usher the phase and phase voltage with neutrally on 3-phase electric network in accurate figure, informative and realtime. The watcher of stability process abaut 3-phase electrics network in electronic can do to use transduser with three single phase transformator in way configuration, by using RS232 interface for data communications of PC and measure module. System examination to ability of application program 3-phase datalogger.exe run by PC as regulator process the datalogger voltage 3-phase watched. In this examination, result of voltage monitoring will be presented in separate linearity graph for the tension of test the R-N, S-N, T-N, RS, ST And TR com-paring with the time depth perception.